1997
DOI: 10.1080/095281397147068
|View full text |Cite
|
Sign up to set email alerts
|

AuRA: principles and practice in review

Abstract: This paper reviews key concepts of the Autonom ous Robot Architecture (AuRA). Its structure, strengths, and roots in biology are presented. AuRA is a hybrid deliberative} reactive robotic architecture that has been developed and re® ned over the past decade. In this article, particular focus is placed on the reactive behavioural com ponent of this hybrid architecture. Various real world robots that have been im plem ented using this architectural paradigm are discussed, including a case study of a multiagent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(122 citation statements)
references
References 34 publications
0
119
0
3
Order By: Relevance
“…However, these do not address the high-level elements of cognition, knowledge representation, reasoning, and planning. Still others (such as AuRA [10] and RCS [11]) are hybrid architectures designed to combine high-level planning with low-level behaviors. The review of this architectures showed that the hybrid scheme has the best performing supervisory control architecture and it is more prosperous and promising dealing with unknown, dynamic navigation problem.…”
Section: Discussion Of Control Architecturesmentioning
confidence: 99%
“…However, these do not address the high-level elements of cognition, knowledge representation, reasoning, and planning. Still others (such as AuRA [10] and RCS [11]) are hybrid architectures designed to combine high-level planning with low-level behaviors. The review of this architectures showed that the hybrid scheme has the best performing supervisory control architecture and it is more prosperous and promising dealing with unknown, dynamic navigation problem.…”
Section: Discussion Of Control Architecturesmentioning
confidence: 99%
“…Alternative approaches to the synthesis of MRS controllers can be found in evolutionary methods [8] and learning methods [16,19]. There also exist a number of MRS design environments, control architectures, and programming languages which assist in the design of task-achieving coordinated MRS [17,2,19,1].…”
Section: Related Workmentioning
confidence: 99%
“…Arkin and Balch (1997) in their AuRA architecture proposed a homeostatic adaptation system that modifies the performance of the overall motor response according to the level of internal parameters such as battery or temperature. Another work that includes a homeostatic adaptation mechanism is the proposal by Low et al (2002) who introduced it to regulate the dynamic behavior of the robot during task execution.…”
Section: Homeostatic Image Stabilizationmentioning
confidence: 99%